Family Domestic Violence: Impact on Children in Lusaka, Zambia - , Mwenso Mwandu; , Kusanthan Thankian; , Gaurav B. Menon; , Sidney O. C. Mwaba; , J. Anitha Menon (Archives of Current Research International, 2020)
Aim: To explore the experiences of children exposed to domestic violence in Lusaka District, Zambia. Study Design: A qualitative exploratory approach was adopted for this study. Place and Duration of the Study: The study took place in Lusaka district over a period of 8 months. The study population included domestic violence survivor children and their parents. The study sample consisted of fifty-two participants divided into thirty children (boys and girls), sixteen parents or guardians, and six key informants. Data was collected using detailed interviews with children and key informants, while focus group discussions were conducted with the parents or guardians. Results: The findings of the study revealed that children were exposed to different forms of domestic violence including physical abuse, emotional (verbal) abuse, and economic abuse. The children were both witnesses and victims of domestic violence. The study also revealed that exposure to violence had negative effects on the children such as physical injury, fear and anxiety, loss of confidence and self-esteem, academic under performance, guilt and shame, and poor relationships with peers and parents. Conclusion and Recommendations: Domestic violence is still prevalent in Lusaka District and has negative long-term effects on children who witness it and are victimised by it. Interventions are necessary to address the size, nature, and complexity of the problem. It is recommended that professionals who have regular contact with families and children, including teachers, child care workers, health and mental health care providers, law enforcement officers, child welfare workers, and court officials should receive ongoing training on domestic violence and its impact on children, and necessary interventions to combat it.